2019
DOI: 10.1111/jep.13107
|View full text |Cite
|
Sign up to set email alerts
|

GheOP3S tool and START/STOPP criteria version 2 for screening of potentially inappropriate medications and omissions in nursing home residents

Abstract: Rationale, aims, and objective: There is limited information about the comparative effectiveness of the START/STOPP (Screening Tool of Older Person's Prescriptions/Screening Tool to Alert doctors to Right Treatment) criteria and the Ghent Older People's Prescriptions community Pharmacy Screening tool (GheOP 3 S tool) for the screening of potentially inappropriate prescribing (PIP) in the geriatric population. Considering this, the aim of this study was to compare the ability of the START/STOPP criteria and Ghe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(46 citation statements)
references
References 31 publications
3
41
2
Order By: Relevance
“…These results are in agreement with those obtained in other similar studies carried out in Portugal and other European countries. 5,[29][30][31]33,38,41 In our study, in contrast to the others performed in Portugal, alprazolam and lorazepam were the two drugs most commonly prescribed as PIMs. In the study performed in pharmacies in Lisbon, diazepam and ticlopidine were the drugs associated with inappropriateness.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…These results are in agreement with those obtained in other similar studies carried out in Portugal and other European countries. 5,[29][30][31]33,38,41 In our study, in contrast to the others performed in Portugal, alprazolam and lorazepam were the two drugs most commonly prescribed as PIMs. In the study performed in pharmacies in Lisbon, diazepam and ticlopidine were the drugs associated with inappropriateness.…”
Section: Discussioncontrasting
confidence: 85%
“…A study performed in elderly patients that visited their primary care physician showed that the absence of antiplatelet therapy was, also, a highly ranked PPO based on START criteria. 38 Another important group with omissions was the musculoskeletal system medication, but in our study, it was not attributed to the absence of vitamin D, rather to the absence of a bone anti-resorptive or anabolic therapy, in contrast to the study performed in nursing homes located in the region of Lisbon and Alentejo. 30 In the analysis of medical data, we did not detect any contraindication to the use of this class of drugs.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…Recent research has demonstrated a high PIP prevalence among older patients in primary care when medication reviews were performed with the GheOP 3 S-tool [23][24][25][26][27][28]. A potential impact on the number of potentially inappropriate medications and the anticholinergic/sedative medication burden was shown after multidisciplinary medication reviews with the GheOP 3 S-tool [25,26].…”
Section: Key Pointsmentioning
confidence: 99%